SISTEM INFORMASI AKUNTANSI PADA MADRASAH TSANAWIYAH AL-IKHLAS SOE KABUPATEN TTS PROVINSI NTT - Mutia Lestari; Emerensye S Y Pandie; Bertha S Djahi (Universitas Nusa Cendana, 2022)
School financial accounting activities are one of the important activities in every educational institution. The Madrasah Tsanawiyah (MTs) Al-Ikhlas Soe, TTS district, NTT province also carried out this activity but it was still done manually which had to be recorded every time a financial accounting transaction was carried out. Therefore, the researchers designed and built a web that aims to enable schools to record accounting transactions through a computerized system which then produces accounting data reports for student tuition payments, school enrollment payments, honorary teacher salaries and school financial cash flows. The method used is the software development life cycle (SDLC) method, which is one method with a characteristic where each phase of work is carried out must be done first before proceeding to phase next, thus the results will focus on each phase so that the work is carried out optimally because there is no parallel work. This study uses two tests of the system, namely blackbox which focuses on testing the functional specifications of the system software, and testing questionnaires to get responses or answers from respondents, namely teachers from MTs Al-Ikhlas Soe regarding the system that has been created. With these two tests, this application system gets a 100% test score percentage using blackbox this is because the functionality of the software runs as expected and also gets an average percentage test value of 83% or 80% using questionnaire testing.